Barriers to the implementation and uptake of simulation-based training programs in general surgery: a multinational qualitative study. - Hosny,SG; Johnston,MJ; Pucher,PH; Erridge,S; Darzi,A (Journal of Surgical Research, 2017)
BACKGROUND: Despite evidence demonstrating the advantages of simulation training in general surgery, it is not widely integrated into surgical training programs worldwide. The aim of this study was to identify barriers and facilitators to the implementation and uptake of surgical simulation training programs. METHODS: A multinational qualitative study was conducted using semi-structured interviews of general surgical residents and experts. Each interview was audio recorded, transcribed verbatim, and underwent emergent theme analysis. All data were anonymized and results pooled. RESULTS: A total of 37 individuals participated in the study. Seventeen experts (Program Directors and Surgical Attendings with an interest in surgical education) and 20 residents drawn from the United States, Canada, United Kingdom, France, and Japan were interviewed. Barriers to simulation-based training were identified based on key themes including financial cost, access, and translational benefit. Participants described cost (89%) and access (76%) as principal barriers to uptake. Common facilitators included a mandatory requirement to complete simulation training (78%) and on-going assessment of skills (78%). Participants felt that simulation training could improve patient outcomes (76%) but identified a lack of evidence to demonstrate benefit (38%). There was a consensus that simulation training has not been widely implemented (70%). CONCLUSIONS: There are multiple barriers to the implementation of surgical simulation training programs, however, there is agreement that these programs could potentially improve patient outcomes. Identifying these barriers enable the targeted use of facilitators to deliver simulation training programs.